2009
DOI: 10.1091/mbc.e08-12-1219
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic Tail of GM3 Synthase Defines Its Subcellular Localization, Stability, and In Vivo Activity

Abstract: GM3 synthase (SAT-I) is the primary glycosyltransferase responsible for the biosynthesis of ganglio-series gangliosides. In this study, we identify three isoforms of mouse SAT-I proteins, named M1-SAT-I, M2-SAT-I, and M3-SAT-I, which possess distinct lengths in their NH 2 -terminal cytoplasmic tails. These isoforms are produced by leaky scanning from mRNA variants of mSAT-Ia and mSAT-Ib. M2-SAT-I and M3-SAT-I were found to be localized in the Golgi apparatus, as expected, whereas M1-SAT-I was exclusively found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 57 publications
(68 reference statements)
1
30
0
Order By: Relevance
“…Amino acid substitution analysis revealed that arginine (R) residues within the CT of Mnn9p, conforming to a canonical R-based COPI-binding motif [66,78], were required for retrieval. Similarly, a recent study by Uemura et al [74] identified an R-based motif in the CT of GM3 synthase that was required for the robust re-cycling of this enzyme from the Golgi to the ER.…”
Section: The Role Of the Cytoplasmic Tail In Glycosyltransferease Locmentioning
confidence: 79%
See 2 more Smart Citations
“…Amino acid substitution analysis revealed that arginine (R) residues within the CT of Mnn9p, conforming to a canonical R-based COPI-binding motif [66,78], were required for retrieval. Similarly, a recent study by Uemura et al [74] identified an R-based motif in the CT of GM3 synthase that was required for the robust re-cycling of this enzyme from the Golgi to the ER.…”
Section: The Role Of the Cytoplasmic Tail In Glycosyltransferease Locmentioning
confidence: 79%
“…However, the CTs of glycosyltransferases lack canonical COPI-binding motifs so how can these proteins be selected for packaging into COPI coated vesicles? Several recent studies have identified motifs in the CTs of glycosyltransferases that appear to be important for maintaining their steady state distributions [66,74,75], and proteins that bind to the CTs [75][76][77].…”
Section: The Role Of the Cytoplasmic Tail In Glycosyltransferease Locmentioning
confidence: 99%
See 1 more Smart Citation
“…encoded the enzyme with the longest cytoplasmic region among several transcript variants (24). GM3 synthase-expressing cells (rGM3S) showed complete resistance to Stx1 even at higher concentrations (Fig.…”
Section: Isolation Of Cdnas To Confer Resistance To Stx-induced Cellmentioning
confidence: 99%
“…3, A-D). GM3Syn may occur in alternatively spliced forms (34). Because RT-PCR analysis showed that both Namalwa and Ramos cells expressed the longer isoform of GM3Syn, we used the cDNA of this isoform for further examinations.…”
Section: Dominant Effect Of Cd77syn On Gsl Expression In B Cells-mentioning
confidence: 99%